Influence of Diet, Sex, and Viral Infections on the Gut Microbiota Composition of Spodoptera exigua Caterpillars - Martínez-Solís, María; Collado, María Carmen; Herrero, Salvador (Frontiers in Microbiology, 2020)
Gut microbiota plays essential roles in processes related with metabolism, physiology and immunity in all organisms including insects. In the present work we have performed a broad analyses of gut microbiota of Spodoptera exigua, a major agricultural pest. We have analysed the influence of multiple parameters such as the diet, geographic location, sex, or viral infections on the gut microbiota composition of S. exigua caterpillars. Our study has revealed a high variability in bacterial composition among individuals and a major influence of the environmental bacteria (including the acquired through the diet) on the gut microbiota composition, supporting previous studies that claim the lack of resident microbiota in caterpillars. Previous studies in laboratory-reared insects have shown that changes in the gut bacterial composition of caterpillars affects to the insecticidal properties of entomopathogenic virus and bacteria. Our study has revealed different microbiota composition in field insects carrying a natural viral infection with the Spodoptera exigua nucleopolyhedrovirus (SeMNPV) and/or the Spodoptera exigua iflavirus 1 (SeIV1). Few taxa can be specifically associated to the infection, suggesting the influence of the microbiota on the infective process of these natural pathogens and providing new strategies for management of insect pests.